2016
DOI: 10.1159/000452787
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoabdominal Asynchrony Is Not Associated with Oxyhemoglobin Saturation in Recovering Premature Infants

Abstract: Background: Recovering premature infants are at risk for hypoxemia and lack of synchrony between their rib cage and abdomen due to airflow obstruction and poor respiratory compliance. Thoracoabdominal asynchrony (TAA) is a useful marker of resistive and elastic lung properties. Whether TAA predicts oxygenation is unknown. Objectives: We investigated oxyhemoglobin saturation (SpO2%) and TAA (phase angle, φ) in preterm infants with/without high-humidity nasal cannula (HHNC). Methods: A cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…studies, we did not directly measure Tpef/Te with a pneumotachometer; rather, it was derived from changes in the sum of thoracic and abdominal expansion over time, changes in flow whose detection could be delayed when the measurements rely on rib cage or abdominal excursion. Finally, among infants studied at 32 weeks PMA, it has been shown that some infants are able to keep their Sp O 2 % greater than 90% in room air, despite having marked asynchrony, with PA much greater than 80 8 in many cases (44). In summary, we have shown that extremely low GA neonates breathing ambient air or on low-flow nasal cannula support have abnormal tidal breathing patterns, but these patterns do not differ between infants with and without BPD.…”
Section: Original Researchmentioning
confidence: 96%
“…studies, we did not directly measure Tpef/Te with a pneumotachometer; rather, it was derived from changes in the sum of thoracic and abdominal expansion over time, changes in flow whose detection could be delayed when the measurements rely on rib cage or abdominal excursion. Finally, among infants studied at 32 weeks PMA, it has been shown that some infants are able to keep their Sp O 2 % greater than 90% in room air, despite having marked asynchrony, with PA much greater than 80 8 in many cases (44). In summary, we have shown that extremely low GA neonates breathing ambient air or on low-flow nasal cannula support have abnormal tidal breathing patterns, but these patterns do not differ between infants with and without BPD.…”
Section: Original Researchmentioning
confidence: 96%
“…Two reviewers (AdMN and ATdCS) will independently assess the risk of bias using the following domains of the PEDro scale: eligibility criteria, random allocation, concealed allocation, baseline comparability, blinding of participants, blinding of therapists, blinding of assessors, adequate follow-up, intention-to-treat analysis, betweengroup comparisons and measures of variability. The total scores of the scale range from 0 to 10, and risk of bias will be interpreted as high (0-3), moderate (5-7) or low (8)(9)(10). 16 Results will be presented in a table containing the name of authors and scores obtained on each item of the PEDro Scale.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…In contrast, non-conventional techniques are usually employed according to anatomical and physiological differences of each age group. [4][5][6] Although conventional and nonconventional physiotherapy are commonly used in neonatal intensive care units to improve secretion mobilisation and thoracoabdominal repercussion, [5][6][7][8][9][10][11][12] the effects on pulmonary mechanics of newborns are still nuclear. Therefore, this systematic review aims to evaluate the effects of conventional and non-conventional respiratory physiotherapies, respiratory pattern, pulmonary…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, the occurrence of periodic respiratory patterns, characterized by periods of insufficient breathing, pauses, or apneas, tends to decline with gestational age. 29 Brennan et al 30 investigated the TA asynchrony in children at 32 weeks of postmenstrual age through the RIP and reported an asynchronous TA pattern in preterm infants regardless of the need for ventilatory support or oxygen therapy. Another outcome of our study, although the difference was not statistically significant when compared to the PTG, is the occurrence of paradoxical TA pattern in 37% of the breathing cycles in the FTG.…”
Section: F I G U R E 3 Thoracoabdominal Synchrony Classificationmentioning
confidence: 99%